1988
DOI: 10.1111/j.1365-2273.1988.tb00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Local versus general anaesthetic in the management of the fractured nose

Abstract: Displaced fractured noses are usually manipulated under general anesthetic. The appearances of fractured noses were assessed and the airways measured by rhinomanometry before and after nasal manipulation in 29 patients. Seventeen received a local anaesthetic (LA) and 12 a general anaesthetic (GA) for the manipulation. Patients were generally pleased with the outcome and there were no significant differences between results in the 2 groups. Bony manipulation did not affect the nasal airway. Local anaesthesia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 5 publications
4
44
0
1
Order By: Relevance
“…The present study reports a high rate of patient satisfaction of 91% with the procedure itself, although fewer patients agreed that CNR helped with the appearance of their nose (65.5%) or nasal breathing (49.0%), which may be due to recall bias. Furthermore, as many patients would undergo the procedure again (89.7%), the anecdotal evidence that CNR may frighten a patient to further intervention seem unfounded in the study cohort . Although a minority of patients sought or were considering further operative intervention, in conversation with patients, fear of the procedure did not seem to play a significant role.…”
Section: Discussionmentioning
confidence: 92%
“…The present study reports a high rate of patient satisfaction of 91% with the procedure itself, although fewer patients agreed that CNR helped with the appearance of their nose (65.5%) or nasal breathing (49.0%), which may be due to recall bias. Furthermore, as many patients would undergo the procedure again (89.7%), the anecdotal evidence that CNR may frighten a patient to further intervention seem unfounded in the study cohort . Although a minority of patients sought or were considering further operative intervention, in conversation with patients, fear of the procedure did not seem to play a significant role.…”
Section: Discussionmentioning
confidence: 92%
“…Watson et al (16) suggested that a patient's fear of a second general anesthetic may contribute to the patient's statement.…”
Section: Discussionmentioning
confidence: 99%
“…In certain hospitals the procedure of closed manipulation is carried out under local anaesthetic (Watson et al, 1988) while a proportion of surgeons prefer to manipulate the fracture under general anaesthetic (Dickson & Sharpe 1987). Some authors strongly believe that if the radiographs show displacement the nose should be manipulated even if it looks straight (Schultz 1970, Murray & Maran 1980.…”
Section: Discussionmentioning
confidence: 99%